2012
DOI: 10.3233/idt-2012-0138
|View full text |Cite
|
Sign up to set email alerts
|

Assessing operator strategies for real-time replanning of multiple unmanned vehicles

Abstract: Abstract. Future unmanned vehicles systems will invert the operator-to-vehicle ratio so that one operator controls a decentralized network of heterogeneous unmanned vehicles. This study examines the impact of allowing an operator to adjust the rate of prompts to view automation-generated plans on system performance and operator workload. Results showed that the majority of operators chose to adjust the replan prompting rate. The initial replan prompting rate had a significant framing effect on the replan promp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Although it would be advantageous for the system to always run its "best" plan, a replanning rate that imposes too high a workload on the human operator and prevents value-added contributions to the plan would be a disadvantage. Cummings, Clare, and Hart (2010) and Clare, Maere, and Cummings (2012) report on replanning strategies and rates, finding that moderate rates and compliance with planner recommendations generally led to better performance and lower workloads.…”
Section: Cooperative Plannersmentioning
confidence: 99%
“…Although it would be advantageous for the system to always run its "best" plan, a replanning rate that imposes too high a workload on the human operator and prevents value-added contributions to the plan would be a disadvantage. Cummings, Clare, and Hart (2010) and Clare, Maere, and Cummings (2012) report on replanning strategies and rates, finding that moderate rates and compliance with planner recommendations generally led to better performance and lower workloads.…”
Section: Cooperative Plannersmentioning
confidence: 99%
“…It should be noted that this assumption does not hold for all systems, as previous studies have shown that frequent human intervention can potentially have a negative impact on automation (Beck, Dzindolet, and Pierce 2005;Parasuraman and Riley 1997), as some decentralised algorithms may need time to stabilise (Walker et al 2012). The automation in the multiple UAV control test bed used to validate CHAS has been found to be provably good, but suboptimal (Choi, Brunet, and How 2009), and previous experiments have shown that a moderate rate of intervention results in higher performance than a low frequency of intervention (Clare, Maere, and Cummings 2012;Cummings, Clare, and Hart 2010).…”
Section: The Chas Sd Modelmentioning
confidence: 93%
“…For mixed-initiative teams, the interactive nature of the planning process is dependent on both the capabilities of the team members and the task or mission needs. In general, human intervention in a control loop for route planning can improve the quality of the IA-generated plan [3]. This dynamic assumes that humans and IAs have different but valuable and often complementary capabilities.…”
Section: Route Planning Mechanismsmentioning
confidence: 99%
“…Replanning frequency generally produces inconsistent effects on mission performance metrics. Some studies [4,5] have found that increased replanning frequency degrades performance, while others [3] have concluded that frequent replanning improves performance. These effects are typically attributed to changes in workload, and they interact with the replanning duration (i.e., the amount of time the human spends replanning the route during each trial) such that replanning improves performance but only if done rapidly.…”
Section: Analysis 1: Consensus In Spatial Mental Modelsmentioning
confidence: 99%